Analisis Yuridis Penyelesaian Sengketa Desain Industri Eco Bottle (Studi Putusan Nomor 594 K/Pdt.Sus-Hki/2017) - Syarafina Rahayu Fitri (Jurnal Perspektif Hukum, 2022)
The industrial design lawsuit between Dart Industries, INC as a company wholly owned by Tupperware Brands Corporation, the industrial design case for Tupparware's Eco Bottle and the Defendant who owns the Bio Life Products has been decided with a decision Number 594 K/PDT.SUS-HKI/2017. Discusses how the lawsuit mechanism for the cancellation of industrial designs as one of the areas of Intellectual Property Rights, What are the legal consequences of using industrial designs without rights that have similarities with industrial designs registered under Law Number 31 of 2000 concerning Industrial Designs, How is legal protection for PT Dart Industries as a user of Industrial Design in an Industrial Design dispute with Bio Life products based on the decision of the Supreme Court Number 594 K/Pdt.Sus-HKI/2017. This type of research is normative legal research, where the approach to the problem is carried out by reviewing the applicable laws and regulations. The research results obtained, namely the absence of a substantive examination of the registration of industrial designs, the non-fulfillment of novelty elements in an industrial design and the absence of an explanation of the basic similarities in the Industrial Design Law. The legal consequences of using industrial designs without rights in accordance with the provisions of Article 46 of the Industrial Design Law, the holders of industrial design rights or licensees can sue the infringing party. The lawsuit filed by the Plaintiff PT. Dart Industri as the owner of the Eco Bottle beverage bottle industrial design. The judge had different basic considerations in passing the decision on the dispute over the shape of the Tupperware beverage bottle, namely in the Supreme Court's Decision Number: 594K/Pdt.Sus-HKI/2017, the Judge stated that it was true that the shape of the Biolife Borneo bottle had the same industrial design as the Tupperware bottle owned by PT. Dart Industries while the Judge in the Supreme Court Decision Number: 874K/Pdt.Sus.HKI/2017, stated that the shape of the Biolife Borneo bottle does not have the same industrial design as the Tupperware bottle owned by PT. Dart Industries.